Circulating TGF-β Pathway in Osteogenesis Imperfecta Pediatric Patients Subjected to MSCs-Based Cell Therapy - Infante, Arantza; Cabodevilla, Leire; Gener, Blanca; Rodríguez, Clara I. (Frontiers in Cell and Developmental Biology, 2022)
Osteogenesis Imperfecta (OI) is a rare genetic disease characterized by bone fragility, with a wide range in the severity of clinical manifestations. The majority of cases are due to mutations in COL1A1 or COL1A2, which encode type I collagen. There is no cure for OI and real concerns exist for current therapeutic approaches, mainly antiresorptive drugs, regarding their effectiveness and security. Safer and effective therapeutic approaches are demanded. Cell therapy with mesenchymal stem cells (MSCs), osteoprogenitors capable of secreting type I collagen, has been tested to treat pediatric OI with encouraging outcomes. Another therapeutic approach currently under clinical development focuses on the inhibition of TGF-β pathway, based on the excessive TGF-β signaling found in the skeleton of severe OI mice models, and the fact that TGF-β neutralizing antibody treatment rescued bone phenotypes in those OI murine models. An increased serum expression of TGF-β superfamily members has been described for a number of bone pathologies, but still it has not been addressed in OI patients. To delve into this unexplored question, in the present study we investigated serum TGF-β signalling pathway in two OI pediatric patients who participated in TERCELOI, a phase I clinical trial based on reiterative infusions of MSCs. We examined not only the expression and bioactivity of circulating TGF-β pathway in TERCELOI patients, but also the effects that MSCs therapy could elicit. Strikingly, basal serum from the most severe patient showed an enhanced expression of TGF-β superfamily members and increased TGF-β bioactivity, which were modulated after MSCs therapy.